Anti-ISIS Humor: Cultural Resistance of Radical Ideology. (2nd January 2016) - Al-Rawi, Ahmed
ABSTRACT: After the release of ISIS's 'Salil Al-Sawarem' promotional and motivational video with its famous religious chant, hundreds of Arab YouTubers started mocking it by editing its chant and including it in funny dancing clips which they called 'the popular edition'. Also, some Arabic and Kurdish TV channels produced shows that aimed at mocking the radical group. Since ISIS regards dancing as a religious taboo, these popular and official media productions represent a cultural resistance force and a rejection of ISIS and its extremist ideology. I argue in this article that these active involvements in ridiculing, countering, and discrediting the terrorists' ideology are cultural resistance efforts that aim at countering terrorism and raising awareness about its dangers in the Middle East region.